2010
DOI: 10.1203/pdr.0b013e3181dcd580
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Respiratory Support of Juvenile Rabbits by High-Amplitude Bubble Continuous Positive Airway Pressure

Abstract: Bubble continuous positive airway pressure (B-CPAP) applies small-amplitude, high-frequency oscillations in airway pressure (⌬P aw ) that may improve gas exchange in infants with respiratory disease. We developed a device, high-amplitude B-CPAP (HAB-CPAP), which provides greater ⌬P aw than B-CPAP provides. We studied the effects of different operational parameters on ⌬P aw and volumes of gas delivered to a mechanical infant lung model. In vivo studies tested the hypothesis that HAB-CPAP provides noninvasive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 23 publications
(14 reference statements)
0
47
0
Order By: Relevance
“…With more area between the air-water seal (the size of the bubble breaking off the tube), a larger amount of energy is transmitted to the pressure waves traveling back through the system into the patient. This phenomenon was discussed by DiBlasi et al 22 in a study investigating highamplitude bubble CPAP in an attempt to explain the large ⌬P aw observed in a 135°expiratory limb configuration. As a result, by allowing more energy to transmit to the air column, there is a greater chance that more frequencies will receive sufficient energy to travel through the lung.…”
Section: Discussionmentioning
confidence: 96%
“…With more area between the air-water seal (the size of the bubble breaking off the tube), a larger amount of energy is transmitted to the pressure waves traveling back through the system into the patient. This phenomenon was discussed by DiBlasi et al 22 in a study investigating highamplitude bubble CPAP in an attempt to explain the large ⌬P aw observed in a 135°expiratory limb configuration. As a result, by allowing more energy to transmit to the air column, there is a greater chance that more frequencies will receive sufficient energy to travel through the lung.…”
Section: Discussionmentioning
confidence: 96%
“…The HAB-CPAP device, which has been described in greater detail previously (5), is similar to a B-CPAP device, with the modification that the angle of the gas exit tubing, or bubbler, can be adjusted (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we demonstrated that HAB-CPAP could provide noninvasive support, via nasal prongs, to spontaneously breathing, lung-lavaged juvenile rabbits, with lower work of breathing and higher PaO 2 levels than were observed in the same animals supported with B-CPAP at identical mean airway pressures (MAPs) (5).…”
mentioning
confidence: 99%
“…In a neonatal lung model affixed with leaky nasal prongs, the high-amplitude bubble-CPAP device adjusted with the outlet tubing at 135°, in relation to the water surface level, was found to deliver similar tidal volumes as those previously measured during HFOV in infants. 45 In addition, it was demonstrated that high-amplitude bubble-CPAP provides noninvasive support, via nasal prongs, to spontaneously breathing, lung-lavaged juvenile rabbits with lower WOB (P Ͻ .001) and higher P aO 2 (P Ͻ .007) than were observed in the same animals supported with bubble nasal CPAP at identical mean airway pressures. 45 Two rabbits supported by high-amplitude bubble-CPAP became apneic with normal P aCO 2 and vital signs.…”
Section: Noninvasive Ventilationmentioning
confidence: 96%
“…45 In addition, it was demonstrated that high-amplitude bubble-CPAP provides noninvasive support, via nasal prongs, to spontaneously breathing, lung-lavaged juvenile rabbits with lower WOB (P Ͻ .001) and higher P aO 2 (P Ͻ .007) than were observed in the same animals supported with bubble nasal CPAP at identical mean airway pressures. 45 Two rabbits supported by high-amplitude bubble-CPAP became apneic with normal P aCO 2 and vital signs. High-amplitude bubble-CPAP may represent a relatively simple new strategy for supporting a greater fraction of neonates who would otherwise fail nasal CPAP and require invasive mechanical ventilation.…”
Section: Noninvasive Ventilationmentioning
confidence: 96%